THE RELATIONSHIP BETWEEN THE IMPLEMENTATION OF COUNSELING GUIDANCE AND THE DISCIPLINE OF MOTORCYCLE ENGINEERING & BUSINESS STUDENTS AT SMK MUHAMMADIYAH 1 PATUK GUNUNGKIDUL - Zaman, Fajrin Sidiq Muzaffarul; Riyadi, Andrian; Dewangga, Andrian Wisnu (Pendidikan Vokasional Teknologi Otomotif, Universitas PGRI Yogyakarta, 2024)
This research is a type of correlational research. This research was conducted at SMK Muhammadiyah 1 Patuk Gunungkidul. The purpose was used to see what the implementation of BK/BP was like in the TBSM department, as well as to see how high the relationship between guidance & counseling, and discipline in the TBSM department. Only 120 students majoring in motorcycle engineering and business were the research subjects. Data on the implementation of BK/BP on student discipline was collected through questionnaires, data collection on the implementation of BK/BP programs using documents and pictures of students who do not obey school rules. Research hypothesis questions were answered using product moment correlation analysis. The results of the study explained that guidance and counseling are well implemented at SMK Muhammadiyah 1 Patuk, and showed that there is a positive and significant relationship between guidance & counseling services and student behavior discipline. An r value of 0.351 (p = 0.05) was found through correlation calculations, indicating a weak positive relationship. A positive relationship means student discipline will increase as guidance and counseling services increase, and vice versa. It can be concluded that guidance and counseling services can improve student discipline. To make the research findings more generalizable, it is suggested that future studies with similar titles do so by testing a larger sample. Keywords: Guidance and Counseling, Discipline, Relationship